Identifikasi Karakteristik Penghuni dan Unit Hunian Pada Rusunawa Bulusidokare di Kabupaten Sidoarjo - Putri, Hilda Fachriza; Soemarwanto, Dadoes; Istijanto, Suko (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2024)
Population growth is increasing every year, which can lead to an increase in demand for housing needs. Therefore, efficiency in the utilization and use of land in urban areas can be done vertical housing development, as an option to solve the problem of housing needs on limited land, easily accessible to people in Sidoarjo Regency who have lower middle income (MBR). In collecting data in this research on the object of Rusunawa Bulusidokare, namely the observation method (observation) and the review method (survey), namely by interview. To obtain data related to residential units, using the observation method. As for the review method (object survey) carried out by means of face-to-face interviews, in order to obtain data related to the characteristics of rusunawa residents when using residential units based on occupant behavior. The characteristics of the residential unit in the Bulusidokare Simple Rental Flat (Rusunawa) Sidoarjo Regency are residential units by utilizing space based on an understanding of the needs of each occupant of one residential unit of the flat.